A new species of Cryptocellus (Arachnida, Ricinulei) from the Kofán Territory in southwestern Colombia - Botero-Trujillo, Ricardo; Pérez, Gustavo A. (Zootaxa, 2009)
Cryptocellus luisedieri sp. nov. is described from a male specimen obtained from leaf litter in the Kofán Territory, southwestern Colombia. The new species exhibits a series of interesting morphological features including the presence of cuticular pits and a unique shape of the male copulatory apparatus. The new species, which is the first ricinuleid found in the southern Colombian Andes, brings to seven the number of species of Cryptocellus Westwood, 1874 known to occur in Colombia and to 66 the number of extant species of this rare arachnid order. A male-based key to the identification of the Colombian ricinuleid species and a map showing their known distribution are included.